Efektifitas Terapi Nature Sound Instrumental dengan Kombinasi Terapi Pijat Kaki untuk Meningkatkan Kualitas Tidur pada Pasien NSTEMI - Nurfadhilah, Mardati; Safrudin, Bachtiar (Poltekkes Kemenkes Palembang, 2025)
Background: Non-ST Elevation Myocardial Infarction (NSTEMI) involves partial or subtotal obstruction of the coronary arteries, leading to chest pain. This pain is typically managed with pharmacological therapy, followed by further observation in the Intensive Cardiology Care Unit (ICCU). During their care, nurses assist patients with all activities, which can hinder adaptation to the new environment and increase anxiety, negatively impacting sleep quality. Sleep quality is often neglected, despite being crucial for the healing process. This study aims to analyze the implementation of non-pharmacological interventions, specifically nature sound instrumental therapy and foot massage therapy, to improve sleep quality in NSTEMI patients at RSUD Aji Muhammad Parikesit Tenggarong. Methods: This study employs a case study design involving two NSTEMI patients in the ICCU experiencing sleep disturbances. The respondents received an innovative intervention combining nature sound instrumental therapy and foot massage therapy for 7 hours over three nights. Sleep quality was measured using the Sleep Quality Questionnaire (KKT) before and after the intervention, with scores ranging from 0 to 28, where higher scores indicate better sleep quality.Results: After three nights of intervention, Case I showed an improvement in sleep quality from a score of 10 (poor) to 20 (good), while Case II increased from a score of 12 (poor) to 24 (good). There was a significant enhancement in sleep quality following the combination of nature sound instrumental therapy and foot massage therapy.Conclusion: The innovative intervention combining nature sound instrumental therapy with foot massage therapy is effective in improving sleep quality in NSTEMI patients in the ICCU. This method can be beneficial in nursing care for managing patients with sleep disturbances in the ICCU. The innovative intervention combining nature sound instrumental therapy with foot massage therapy is effective in improving sleep quality in NSTEMI patients in the ICCU. This method can be beneficial in nursing care for managing patients with sleep disturbances in the ICCU.